Single input fuzzy logic for mimo process control - Zainal, Mohammad Amri (2010)
Implementations of Fuzzy Logic Control (FLC) algorithms are often done using a platform which has high performance processors since FLC requires a lot of computation. In the case of a Multi-Input Multi-Output (MIMO) system, the processing time is unacceptable since the fuzzy rules increase exponentially as the number of input increases. This project presents the approach of Single Input Fuzzy Logic Control (SIFLC) algorithm to control an evaporator, which is a MIMO process plant. SIFLC is a simplified version of Fuzzy Logic Control (FLC) that utilizes signed distance method and linear piecewise processing. The simulation is done using both FLC and SIFLC. The result shows that both the input output pairs are almost identical. Although the FLC gave better transient response than the SIFLC, the difference is small and can be neglected in some cases. Most importantly, the SIFLC gave a much faster computation time than the FLC.